Pendampingan ibu balita dalam melakukan deteksi dini stunting melalui skoring menggunakan Kartu Prediksi Stunting Heni (KPSH) - Heni Puji Wahyuningsih (Jurnal Kesehatan Pengabdian Masyarakat (JKPM), 2020)
The problem of stunting or stunting is one of the nutritional problems faced in the world, especially in poor and developing countries. Stunting can have both long- and short-term effects. In 2017 22.2% or around 150.8 million children under five in the world came from ASIA (55%). The prevalence of stunting for stunting in Indonesia is 30.8% in 2018. Early detection of stunting which requires a detailed assessment needs to be packaged in a simple, accurate and inexpensive method, so that the stunting scoring prediction card can be a method that can be used as an aid in detection. stunting. For this reason, it is necessary to create a quality of life for toddlers, maintain and detect developments and growth child well, so it is necessarydetection of the risk of stunting in children under five. UTo achieve this, passistance to mothers of children under five to screen the risk of stunting in children. Community service activities are carried out in stages with the stages of identification, implementation, monitoring, evaluation. Kegtrue this was carried out on the month February 2020. The means required are KPSH stunting screening card (Heni Stunting Prediction Card). The community service activities carried out are in the form ofassisting mothers under five in stunting detection. The provision of materials is tailored to the needsmothertoddler. From the results of the evaluation carried out after training, 85%toddler mother already able to do screening risk of stunting in toddlers, but there are still some mother who do not understand how to be screened risk of stunting onchildren so they need to exercise regularly. Based on the results of the activity, it can be concluded that the community has good enthusiasm so that the service activities can run smoothly